Effect of Xingnaojing injection on cerebral edema and blood-brain barrier in rats following traumatic brain injury - 徐妙 苏伟 徐秋萍 黄卫东 (Chinese journal of traumatology, 2010)
Objective：To explore the effects of Xingnaojing injection on cerebral edema and blood-brain barrier （BBB） in rats following traumatic brain injury （TBI）.Methods： A total of 108 adult male Sprague-Dawley rats were used as subjects and randomly assigned to three groups：sham-operation,TBI and Xingnaojing injection was set up by the improved device of Feeney＇s weightcontent and BBB permeability expressed as Evans blue content were measured at 1, 3, 5 and 7 days after surgery.Results： In sham-operation group, brain water content and Evans blue content in brain tissue were 78.97%±1.22%and 5.13μg±0.71μg. Following TBI, water content in brain tissue was increased significantly at 1, 3, 5 and 7 days （83.49%±0.54%, 82.74%±0.72%, 80.22%±0.68%, 79.21%±0.60%）, being significantly higher than that in sham operation group （P〈0.05）. Evans blue content was increased in TBI group （16.54 μg±0.60 μg, 14.92μg±0.71μg, 12.44 μg ±0.92μg, 10.14μg±0.52 μg） as compared with sham-operation group（P〈0.05）. After treatment with Xingnaojing injection, brain water content decreased as compared with TBI group （81.91%±1.04%, 80.38%±0.72%, 79.54%±0.58%,78.60%±0.77%, P〈0.05）. Xingnaojing injection also reduced the leakage of BBB as compared with TBI group （15.11 μg± 0.63 μg, 13.62 μg±0.85μg, 10.06 μg±0.67 μg, 9.54 μg±0.41 μg,P〈0.05）.Conclusion： Xingnaojing injection could alleviate cerebral edema following TBI via reducing permeability ofBBB.